Factors That Affect The Low Achievement of Students’ English Learning At The Tenth Grade of SMA Muhammadiyah 1 Kotabumi Academic Year 2021/2022 - Rani Juliyasari; Elis Susanti; Dewi Sartipa; Era Aura Valentin; Indah Asmara Putri; Maria Faulinda; Marsella (Edukasi Lingua Sastra, 2023)
The purpose of this study was to determine student achievement and the factors that influence student achievement in the tenth grade English subject at SMA Muhammadiyah 1 Kotabumi for the academic year 2021/2022. The purpose of this study is to describe What are the factors that influence the low English learning achievement of tenth graders at SMA Muhammadiyah 1 Kotabumi? In this study, the researcher used a qualitative descriptive research method. The data of this study were taken from the interviews of tenth grade English teachers and tenth graders. The instrument used in this research was the interview. In this study , the data collection used by the researcher was an in - depth interview technique . The results of this study illustrate that in fact there are two factors that influence students' low achievement in learning English. The two factors are internal factors and external factors. In internal factors there are problems of intelligence, attitude, and motivation, while problems with external factors consist of family environmental, school environmental, and community environmental.